Enhancing secondary metabolite production by Chlorella sorokiniana using an alternative medium with vinasse (Research, Society and Development, 2021)
Microalgae production is expensive and requires high volumes of water and energy. The use of sugar cane vinasse as an alternative medium, has gained attention for microalgae cultivation. In this study, we compared the biomass yield and secondary metabolite production by Chlorella sorokiniana grown in a commercial medium (Sueoka) and versus those grown in a medium prepared with cane vinasse (0.1%) supplemented with N:P:K (20-5-20 g.L-1). Microalgae reached the maximum growth point 14 days faster in the alternative medium. Increased average phenolic compound levels and flavonoid content were found in the vinasse medium (15.28 ± 0.32 mg GAE.g-1 and 72.30 ± 5.28 mg QE. g-1, respectively) compared to that of the commercial medium (6.02 ± 0.13 mg GAE .g-1 and 13.12 ± 1.33 mg QE g-1, respectively). The maximum antioxidant activity (AOA) of C. sorokiniana grown in vinasse medium was 88.05% with an extract concentration of 1500 µg.mL-1, and an IC50 of 357.7 ± 27.35 µg.mL-1. Different factors, such as stress due to chemical oxygen demand (COD), and vinasse-added ions, may have induced variances in secondary metabolite synthesis. Further investigations are needed to explore natural and low cost alternatives to increasing flavonoid yield for the bioprospection of microalgae.